2009
DOI: 10.3892/ijmm_00000200
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate improves nonalcoholic steatohepatitis model mice expressing nuclear sterol regulatory element binding protein-1c in adipose tissue

Abstract: Abstract. We examined whether or not epigallocatechin-3-gallate (EGCG) improves liver injury of nonalcoholic steatohepatitis (NASH) model mice expressing nuclear sterol regulatory element-binding protein 1c in adipose tissue. nSREBP-1c transgenic C57BL6 mice aged 30 weeks were divided into group 1 (no treatment), group 2 (ascorbic acid alone), group 3 (ascorbic acid and 0.05% EGCG), and group 4 (ascorbic acid and 0.1% EGCG). At 42 weeks, we performed measurement of liver weight to body weight, biochemical ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…57 EGCG protects against NASH in the adipose SREBP-1c overexpression model by decreasing the expression of hepatic phosphorylated Akt, phosphorylated inhibitor of nuclear factor kappa-B (NFkB), and phosphorylated NfkB. 104 Consistent with these findings, recently completed studies found that ob/ob mice developed severe liver steatosis with moderate inflammation that was attenuated by GTE. 158 Greater inflammatory cell activation in obese mice was evidenced by greater hepatic expression of inducible nitric oxide synthase, NADPH oxidase, and myeloperoxidase, whereas GTE normalized the expression and activity of these inflammatory enzymes to the level of lean controls.…”
Section: Gte: Protective Effects Against the "Second Hit" Of Nashmentioning
confidence: 77%
See 3 more Smart Citations
“…57 EGCG protects against NASH in the adipose SREBP-1c overexpression model by decreasing the expression of hepatic phosphorylated Akt, phosphorylated inhibitor of nuclear factor kappa-B (NFkB), and phosphorylated NfkB. 104 Consistent with these findings, recently completed studies found that ob/ob mice developed severe liver steatosis with moderate inflammation that was attenuated by GTE. 158 Greater inflammatory cell activation in obese mice was evidenced by greater hepatic expression of inducible nitric oxide synthase, NADPH oxidase, and myeloperoxidase, whereas GTE normalized the expression and activity of these inflammatory enzymes to the level of lean controls.…”
Section: Gte: Protective Effects Against the "Second Hit" Of Nashmentioning
confidence: 77%
“…102 The same dose of EGCG provided to mice overexpressing SREBP-1c for 12 weeks reduced histological evidence of hepatocyte ballooning and Mallory-Denk bodies. 104 EGCG protected against inflammation in these models but did not protect against fibrosis. By contrast, 3% microbially fermented GTE containing primarily ECG and gallocatechin had no effect on inflammation in rats fed a high-fat, choline-deficient diet and given daily intraperitoneal injections of nitrite, but it normalized fibrosis as evidenced by histological findings.…”
Section: Gte: Protective Effects Against the "Second Hit" Of Nashmentioning
confidence: 87%
See 2 more Smart Citations
“…Recent studies have shown a strong correlation between the consumption of green tea and the prevention of NAFLD. Other studies have shown that EGCG reduced the severity of liver injury by reducing circulating insulin, improving insulin sensitivity and attenuating insulin resistance in type 2 diabetes mellitus (T2DM) or NAFLD mice [12][13][14] . Although EGCG reduces circulating insulin, it is not clear whether IDE is involved.…”
Section: Introductionmentioning
confidence: 99%